2020
DOI: 10.1097/sap.0000000000002624
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral Vision Loss After Hyaluronic Acid Injection

Abstract: Vascular occlusion causing vision loss is a rare yet one of the most devastating complications of facial esthetic fillers. In this article, we present a case of unilateral blindness and superficial skin necrosis in a 31-year-old woman after the injection of hyaluronic acid for esthetic purposes. The delicate ocular fundal findings of ophthalmic artery occlusion were demonstrated by ophthalmoscopy, optical coherence tomography, and fluorescein angiography. Magnetic resonance imaging also showed subsequent ische… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…( See table, Supplemental Digital Content 1, which displays information on 165 patients. 44–98 http://links.lww.com/PRSGO/C749).…”
Section: Resultsmentioning
confidence: 99%
“…( See table, Supplemental Digital Content 1, which displays information on 165 patients. 44–98 http://links.lww.com/PRSGO/C749).…”
Section: Resultsmentioning
confidence: 99%
“… 9 One case report of vision loss after forehead injection of HA resulted in permanent loss after 5 months; the authors indicated that HBOT had not been started within 24 h of injury which likely hindered its ability to alter the patient's prognosis. 10 Four additional case reports of visual changes after HA injection treated with HBOT also showed no improvement; however, the exact protocol and timing of HBOT are not given. 11-14 Notably, the immediate injection of hyaluronidase in a few of these cases did not improve visual symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…The main goal is to increase the amount of oxygen dissolved in the plasma. Increased dissolved oxygen works to improve the diffusion distance, supporting oxygen-dependent processes that do not get enough arterial blood supply [53] . One report discussed the case of a 31-year-old woman who received HA filler at the nasal dorsum and developed immediate vision loss in the right eye [54] .…”
Section: Complications Vision Lossmentioning
confidence: 99%